ANALISIS KEPUASAN PELANGGAN PDAM KOTA DENPASAR DITINJAU DARI ASPEK TEKNIS - Haja, Separdi; Norken, I N.; Suputra, I Ketut (JURNAL SPEKTRAN; Vol. 3, No. 1, Januari 2015DO - 10.24843/SPEKTRAN.2015.v03.i01.p04)
Abstract : Regency Water Supply Company (PDAM) of Denpasar city is one of the PDAM that have a healthy predicate from 2009-2012 based on the results by the assessment Development Support Agency of Water Supply System (BPPSPAM). But in fact many customer complaints are heard in the newspaper and electronic media. From PDAM of Denpasar city annual report in 2013, there were 6,738 cases of complaints regarding service and 83.38 percent came from the technical aspect. This research aims to determine the level of customer satisfaction, the indicators that affect customer satisfaction and indicators affecting what should be improved to increase customer satisfaction reviewed from technical aspect. This research was conducted in Denpasar city with the 398 respondents who are household customer PDAM of Denpasar. The analysis took based on the Importance-Performance analysis and Gap analysis. Importance-Performance analysis resulted in indicators of influence and should be improved to increase customer satisfaction. While the Gap analysis  showed the level of customer satisfaction PDAM of Denpasar city. The majority of customer were dissatisfied with the service received from technical aspects. Shown from the Gap of -1.01 and suitability level of performance and the importance is worth 0.76 (less than 1). The level of customer satisfaction PDAM Denpasar city for complaints of the piping aspect (-1.09) is at a low level satisfaction (-1,059 < I < -1,01), while satisfaction level for the water quality (-0.982), water continuity (-0.975), speed installation of new connections (-1.003) and water meters (-0.973) are at moderate levels of satisfaction(-1,01 < I < -0,961). The indicators that affect customer satisfaction are the clarity of the water, smelly water, flavored water, chemical content, hours of availability of water in the life activity, alertness operators in the installation of new connection, reading the water meter, water meter repair damage, and alertness/speed handling of complaints about the piping. Some performance indicators should be improved by the PDAM of Denpasar city to improve customer satisfaction are the clarity of the water, the smell of the water, the availability of water at life activity, alertness operators in the installation of new connections, water meters repair damage, and alertness/speed handling of complaints about the piping.
Keywords: customer PDAM satisfaction, technical aspect, Importance-Performance analysis, Gap analysis.